Internal versus external control of calcium nutrition in kiwifruit. Issue 6 (8th October 2014) - Montanaro, Giuseppe; Dichio, Bartolomeo; Lang, Alexander; Mininni, Alba N.; Nuzzo, Vitale; Clearwater, Michael J.; Xiloyannis, Cristos
Abstract Higher calcium (Ca) concentration in several fleshy fruit including kiwifruit is a pre‐requisite for lower incidence of Ca‐related diseases and improved fruit nutritional value. This review examines the internal and external factors operating along the soil‐to‐fruit pathway that are involved in the uptake and partitioning of Ca in kiwifruit vines. After a brief description of fruit growth and the dynamic of nutrient accumulation during fruit development, the review considers the role of soil Ca concentration and availability, root elongation, mass flow in the apoplast, fruit transpiration, competition between fruit and highly transpiring leaves, weather variables and soil moisture. How fruit morphological and anatomical traits, including skin anatomy, xylem development and hydraulic resistance, influence physiological processes such as transpiration and impact on Ca accumulation is also discussed. The review highlights that approximately 80% of the total Ca content of fruit is accumulated during the early weeks after fruit‐set, suggesting that failure of good fruit Ca nutrition at that time may lead to poor fruit Ca content at harvest. Therefore, based on the analysis of the internal and external factors that influence Ca accumulation, recommendations are made for orchard practices that maximize Ca accumulation in the kiwifruit berry, including optimal pollination, nutrient and irrigation management, and manipulation of canopy architecture.